Indole Synthesis Based On A Modified Koser Reagent1. Issue 28 (28th May 2014) - Fra, Laura; Millán, Alba; Souto, José A.; Muñiz, Kilian
Abstract A new metal‐free method for the rapid and productive preparation of indoles has been developed. This process is based on sterically congested hypervalent iodine compounds of the family of Koser reagents, and iodosobenzene in combination with 2, 4, 5‐tris‐isopropylbenzene sulfonic acid provides the highest yields and fastest reaction times. This reagent alone promotes the chemoselective oxidative cyclization of 2‐amino styrenes to indoles in high yields under mild conditions.